Pengaruh Struktur Modal, Profitabilitas dan Likuiditas Terhadap Nilai Perusahaan pada Sektor Kesehatan di Bursa Efek Indonesia Tahun 2019-2023 - Siti Alifa, Avi Fitri (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
The purpose of this study is to determine the influence of capital structure, profitability, and liquidity on the value of companies in the health sector on the Indonesia Stock Exchange for the period of 2019-2023. The method used in this study is quantitative. The population in this study is 33 companies, the sampling technique used in this study is non-probability sampling with the purposive sampling method, the sample in this study is 29 companies. The data used in this study is secondary data. The analysis method used in this study is multiple linear regression analysis, using SPSS version 26. Capital structure partially has no effect on company value, Profitability and liquidity have a partial effect on company value and capital structure, profitability and liquidity simultaneously have a significant effect on company value in health sector companies on the Indonesia Stock Exchange in 2019-2023. The magnitude of the influence of capital structure, profitability and liquidity on the value of this company is 49.6% and 50.4% influenced by variables outside this study.